A. Cepas. The North of Britannia and the Northt-West of Hispania. An epigraphic comparison. BAR.. International Series. nº 470, 1.989. - RIBAGORDA, Miguel (Gerión. Revista de Historia Antigua, 1990)
Sin resumen